To assess the prevalence of STI/RTI using syndromic case management in the urban health centre area of greater Visakhapatnam municipal corporation, Andhra Pradesh - Ganta, Srinivas Rao; Prasad, K. K. L.; Srinivas, P. J. (International Journal Of Community Medicine And Public Health, 2017)
Background: Sexually transmitted diseases remain a major public health problem in many parts of the world. 340 million new cases of curable STIS occur every year. 75 to 85% are seen in developing countries and rank second as the cause of healthy life lost among women of reproductive age group, after maternal morbidity and mortality. Methods: The study was conducted at Rama Murthy Pantulu Peta in the field area of urban health centre of greater Visakhapatnam Municipal Corporation, Visakhapatnam during September 2015 to October 2016. The study design was a community based descriptive study. Based on the prevalence of STI as stated by National AIDS Control Organization, a sample of 1541 is calculated. Results: The overall prevalence of RTI/STI in our study is 18.88%. The prevalence of symptoms suggestive of STI/RTI among female respondents is found to be 27.97%. Majority of females complained of vaginal discharge (26.68%),vulvas itching (10%), lower abdominal pain (6.34%) followed by abnormal vaginal bleeding (5.91%).The prevalence of symptoms suggestive of RTI/STI is found to be 9.75% among male respondents and majority complained of Urethral Discharge (8.4%) followed by inguinal/scrotal swelling (5.2%). Conclusions: The prevalence of Reproductive tract infections is more in females when compared to males in our study. Health education regarding the sexual and personal hygiene should be targeted to both males and females so as to decrease the prevalence of Sexual transmitted diseases in the urban health centre areas of Visakhapatnam.